Direct measurements and prediction of the particle egress from a vortex-based solar cavity receiver with an open aperture. (15th March 2022) - Tang, Yining; Sun, Zhiwei; Tian, Zhao; Chinnici, Alfonso; Lau, Timothy; Saw, Woei; Nathan, Graham J.
Highlights: Direct measurements of egressed particles through the open aperture of the receiver. The effect of Froude number, Stokes number, receiver orientation on particle egress. Over-ventilation at the outlet port found to be the most significant factor on mitigating particle egress. Despite the particle egress not eliminated, an important step towards a windowless solar reactor/receiver. Abstract: We report direct, in-situ measurements and numerical predictions of the normalised particle egress from a vortex-based particle solar receiver with an open aperture under iso -thermal conditions. These represent an important advancement toward meeting the challenge of developing both a suitable configuration and control strategy for operation of an open-to-atmosphere vortex reactor without significant particle egress. This control strategy induces a net inflow through the aperture by over-ventilating the outlet port as means to mitigate particle egress (here polymethylmethacrylate particles) for one configuration of the device. The influences of the level of over-ventilation, the Froude number and the Stokes number on the overall normalised particle number from the receiver were investigated using a planar laser-based Mie scattering method and computational fluid dynamics. It was found that, although this control strategy can be configured to mitigate particle egress from the vortex-based particle solar receiver with an open aperture, this will require significant over-ventilation of the cavity for the present configuration. The sensitivity analysis also found that slight over-ventilation is the most significant factor on controlling particle egress while significant over-ventilation is less effective considering the impact on thermal performance and the demand of fan power. This represents an important step toward the development of a windowless reactor, although further development of the configuration is needed to achieve efficient mitigation.